Awaru : powiesc - Szymczyk, Wanda (Londyn : Polska Fundacja Kulturalna, 1987)
A novel set in Eastern Africa, the author's intent was to give the reader a true picture of Africa which she experienced in her 16 years there.
Keywords: Africa, East -- Fiction